UPDATED LIGHT ELEMENTS OF 10 RRAB STARS IN THE ANTLIA, CAELUM AND SCULPTOR CONSTELLATIONS - Kolotsey, A.; Atroschenco, M.; Dubrouski, S. A.; Baluk, I. I. (Одеські астрономічні публікації, 2017)
This paper presents the results of verification of the periods and other characteristics of 10 variable stars. The All Sky Automated Survey (ASAS) data have been used in this verification study. 10 RRab stars in the Antlia, Caelum and Sculptor constellations have been investigated. The study was performed using the software package developed by S.A.Dubrouski and V.P.Goranski.